Rainfall runoff simulation using MIKE11 NAM - Shamsudin, Supiah; Hashim, Normala (Faculty of Cvil Engineering, 2002)
Rainfall runoff estimation from a watershed is of vital importance as these values are required in most hydrologic analysis for the purpose of water resources planning. This study deals with Layang River rainfall runoff estimation using MIKE 11 NAM model. The calibration and validation procedures were carried out to provide a satisfactory estimation. The runoff discharges were simulated for a 12-year period (1988-2000). The simulated peak flow occurred in 1992 and 1995 with approximate values of 20.94 m3/s and 18.93 m3/s respectively. The optimum values of the model parameters obtained during the calibration procedure were presented. The reliability of MIKE11 NAM was evaluated based on the Efficiency Index (EI) and Root Mean Square Error (RMSE). The EI and RMSE obtained during this study are 0.75 and 0.08 respectively